2019
DOI: 10.1109/jtehm.2018.2889496
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Clinical Translation of Second Harmonic Microscopy of Meniscal and Articular Cartilage Using a Prototype Nonlinear Microendoscope

Abstract: Previous studies using nonlinear microscopy have demonstrated that osteoarthritis (OA) is characterized by the gradual replacement of Type II collagen with Type I collagen. The objective of this study was to develop a prototype nonlinear laser scanning microendoscope capable of resolving the structural differences of collagen in various orthopaedically relevant cartilaginous surfaces. The current prototype developed a miniaturized femtosecond laser scanning instrument, mounted on an articulated positioning sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Understanding the different stages of the disease progression requires finding new techniques for longitudinal intravital imaging of the articular cartilage. These regions are not easily accessible with microscope objectives, but recent developments of GRIN lenses for the exploration of deep organs and cavities in live animals , as well as the first report on preclinical translation of SHG microscopy to the meniscal and articular cartilage , could provide solutions for this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the different stages of the disease progression requires finding new techniques for longitudinal intravital imaging of the articular cartilage. These regions are not easily accessible with microscope objectives, but recent developments of GRIN lenses for the exploration of deep organs and cavities in live animals , as well as the first report on preclinical translation of SHG microscopy to the meniscal and articular cartilage , could provide solutions for this problem.…”
Section: Discussionmentioning
confidence: 99%
“…As a recent breakthrough in technological advancement, SHM images acquired using a flexible fiber-optic-based probe head possess a quality level comparable to images captured by large bench-top laser-scanning microscopes was demonstrated by Liang et al, that shows a promising potential of SHM for in-vivo arthroscopic applications [17]. In another study Stephen et al, recently demonstrated the pre-clinical translation of SHM using a microendoscope and a prototype of a SHM-based arthroscope for the in-vivo assessment of articular cartilage [16]. A summary of major recent advancements in articular cartilage assessments by SHM are included in Table 1.…”
Section: Current Status: a Short Review Of Recent Advancesmentioning
confidence: 93%
“…Recently, SHM has been demonstrated for real time in-vivo endomicroscopy images with resolution 2.6 µm [16]. The acquired SHM micrographs are capable of detecting microsplits and ultra-structure fibril arrangements of collagen fiber in articular cartilage.…”
Section: Second Harmonic Microscopy For Cartilage Assessmentmentioning
confidence: 99%
See 2 more Smart Citations